The Complete Solution of the Construction Problem of Infinite Frames with Given Redundancy. (10th October 2022) - Hasankhani Fard, Mohammad Ali
Abstract: It is constructed infinite frames with some given redundancy. In this paper, the solution of the construction problem of infinite frames with given redundancy, is completed. More precisely, all possible infinite frame redundancies are characterized.